The trials of Morrigan Crow - Townsend, Jessica, 1985- (Townsend, Jessica, 1985- Nevermoor., 2018)
Born on an unlucky day that leaves her cursed to die on her eleventh birthday, a young girl named Morrigan Crow hopes to avoid her fate by earning a position in the Wundrous Society and thereby securing a safe home in a magical land called Nevermoor. But first she must compete against hundreds of other children in four very dangerous trials.